2019
DOI: 10.1002/ente.201900732
|View full text |Cite
|
Sign up to set email alerts
|

The Synergy of Dilute Pd and Surface Oxygen Species for Methane Upgrading on Au3Pd(111)

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The calculation results show that on the alloy surface Au 3 Pd(111), the hydrogen affinity difference is −1.33 eV (more negative than −0.64 eV), which means that the pre‐adsorbed oxygen atom can strongly help to abstract the hydrogen atom. The mechanisms of methane dissociation on Au 3 Pd(111) are named as the Au pathway (i.e., CH 3 binds with the atop Au) and the Pd pathway (i.e., CH 3 binds with the atop Pd) 58 . Following the Au pathway, the activation energies of the oxygen‐assisted dissociation and the direct dissociation are 1.42 and 1.92 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The calculation results show that on the alloy surface Au 3 Pd(111), the hydrogen affinity difference is −1.33 eV (more negative than −0.64 eV), which means that the pre‐adsorbed oxygen atom can strongly help to abstract the hydrogen atom. The mechanisms of methane dissociation on Au 3 Pd(111) are named as the Au pathway (i.e., CH 3 binds with the atop Au) and the Pd pathway (i.e., CH 3 binds with the atop Pd) 58 . Following the Au pathway, the activation energies of the oxygen‐assisted dissociation and the direct dissociation are 1.42 and 1.92 eV.…”
Section: Resultsmentioning
confidence: 99%
“…C–H bond activation and the DH process on transition-metal (TM) surfaces have been widely investigated for light alkanes, both experimentally and theoretically. For instance, the activation of methane under moderate conditions was only observed on oxygen-precovered Cu surfaces, and using density functional theory (DFT) calculations, it was shown that the activation energy of methane is decreased using promoters such as O*, OH*, O 2 *, and OCH 3 . Promoters for methane activation have also been evaluated on Pd and Au as well as their alloys. , Alkane DH has been studied primarily on Pt catalysts for the nonoxidative process, and investigations targeted Ni and Pd for the ODH process. ,, The direct dissociative chemisorption of propane and iso-butane and their fully deuterated isotopes was studied on the Pt(110) surface, where it was found that the difference in activation energies of C–H and C–D bond cleavage can be attributed to differences in zero-point energy stemming from the two isotopes. …”
Section: Introductionmentioning
confidence: 99%
“…18−21 Promoters for methane activation have also been evaluated on Pd and Au as well as their alloys. 22,23 Alkane DH has been studied primarily on Pt catalysts for the nonoxidative process, and investigations targeted Ni and Pd for the ODH process. 10,13,24−34 The direct dissociative chemisorption of propane and iso-butane and their fully deuterated isotopes was studied on the Pt(110) surface, where it was found that the difference in activation energies of C−H and C−D bond cleavage can be attributed to differences in zeropoint energy stemming from the two isotopes.…”
Section: Introductionmentioning
confidence: 99%